Important Insect Pests on Cabbage in Lao PDR : https://doi.org/10.69692/SUJMRD0802197 - SIBOUNNAVONG, Phoutthasone; SIBOUNNAVONG, Phonesavard; SOYSOUVANH, Phewphan; SOYSOUVANH, Phounsab (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This study was conducted in Xiengkhouang province, Vientiane province, Saravane province, Champasak province, Vientiane Capital, and Plant Protection Center, from January to March 2017. The aims of study were to investigate to major insect pests on cabbage and compared the efficacy of Jeevatu, Jeevatu+botanical pesticide and chemical pesticide to control Diamondback moth in laboratory condition. The study was divided into two treatments: 1) survey important insect pests of cabbage in 3 purposive sampling areas (field)/village, 10 points/rai, and 3 cabbages/point to identify insect pests and survey the life cycle of Diamondback moth of cabbage, and 2) conduct the efficacy experiment of Jeevatu, Jeevatu+botanical pesticide and chemical pesticide to Diamondback moth in laboratory. The experiment was done by Completely Randomized Design (CRD) with 5 treatments and 4 replications. The survey showed that there are 8 species of insect pests on cabbage and the most important species is Diamondback moth (Plutella xylostella) which was found in all provinces that had been survey than followed by striped flea beetle (Phyllotreta striolata), cabbage aphid (Brevicoryne brassicae), cabbage butterfly (Pieris rapae), taro caterpillar (Spodoptera litura), cabbage webworm (Hellula undalis), cabbage looper (Trichoplasia ni) and flea beetle (phyllotreta cruciferae). Life cycle of Diamondback moth was investigated in that laboratory, and it showed that the total of life cycle took about 14-21 days that included 3-5 days for egg stage, 8-12 days for lavae stage, 3-4 days for pupae stage, and 13-31 days of bebeing mature. The efficacy of Jeevatu+Sugar apple leaf extracts, Jeevatu+Neem extracts, and Jeevatu with water for control Diamondback moth indicated that after 5 days sprayed, the mortality percentage was up to 90%, 80% and 57% respectively. For chemical sprayed for 2 days, the mortality percentage was up to 100%. The results of this study showed that the Jeevatu+botanical pesticide can be used as a substitute for substituting chemical in preventing the control Diamondback moth.